The Effect of Interpersonal Communication, Leadership Style, and Training on Teacher Performance at Private Senior High Schools in Serang Regency - Hajar, Siti; Suparmoko, Muhamad; Maliki, Budi Ilham (Economics and Digital Business Review, 2026)
Teacher performance is a fundamental factor in determining the quality of education and the effectiveness of the learning process in schools. In the context of private schools, improving teacher performance is a strategic challenge because it is influenced by organizational dynamics, communication patterns, leadership quality, and competency development systems. This study aims to analyze the influence of interpersonal communication, leadership style, and training on teacher performance in Private Senior High Schools in Serang Regency. The study used a quantitative approach with an explanatory survey design. The population was 137 teachers with a sample of 58 respondents determined using the Slovin formula. Data were collected through a Likert scale questionnaire that had met validity and reliability tests, then analyzed using multiple linear regression in SPSS version 26. The results showed that partially interpersonal communication had no significant effect on teacher performance, while leadership style and training had a positive and significant effect. Simultaneously, the three variables had a significant effect on teacher performance with an Adjusted R Square value of 0.903, indicating that 90.3% of the variation in teacher performance can be explained by the research model. These findings confirm that strengthening principal leadership and optimizing ongoing training programs are priority strategies in improving teacher performance. This research provides an empirical contribution for school managers in formulating evidence-based human resource development policies.